2012
DOI: 10.5539/emr.v1n2p122
|View full text |Cite
|
Sign up to set email alerts
|

Determining Critical Project Success Criteria for Public Housing Building Projects (PHBPS) in Ghana

Abstract: Successive Public Housing Building Project (PHBP) attempts have been unsuccessful due to a number of reasons. Among these is the lack of clearly defined success criteria which guides and measures PHBP success from inception to closure. The adoption and application of project management practice and project success criteria is to deliver projects successfully, attain enhanced output, develop framework to help track key project results and to enable the appropriate allocation of resources. This paper aimed to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…It can unequivocally be stated that the clear understanding of the nature and features of projects is crucial towards its effective management to ensure successful delivery [10]. Mass housing projects (MHPs) share attributes that are significantly different from "one-off " construction building projects [13,19,23]. These attributes of MHPs influence the operational, organisational, and managerial actions during the construction process.…”
Section: Mass Housing Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…It can unequivocally be stated that the clear understanding of the nature and features of projects is crucial towards its effective management to ensure successful delivery [10]. Mass housing projects (MHPs) share attributes that are significantly different from "one-off " construction building projects [13,19,23]. These attributes of MHPs influence the operational, organisational, and managerial actions during the construction process.…”
Section: Mass Housing Projectmentioning
confidence: 99%
“…Unlike many studies that have identified features of "oneoff " traditional construction building projects from different perspectives [1,2,[9][10][11][12], studies on mass housing have primarily admitted to the unique particularities but lacked an attempt to clearly define and determine these features [7,[13][14][15]. Given that, from managerial perspective, organisational and operational task functions are key components of management practice that require much attention if management efficiency is to be achieved, this study aims to determine and classify the unique characteristics of mass housing projects.…”
Section: Introductionmentioning
confidence: 99%
“…The Ghanaian construction industry continues to struggle with a high incidence of project delays and time overruns (Buertey et al 2013). Completing a project on time is still considered a critical success factor in project delivery in the industry (Adinyira et al 2012). Architects' contribution to poor adherence to schedules is often seen in constant delays and postponement of decision meetings, late issue of payment certificates and frequent variation orders, often not at the insistence of the client but rather due to discrepancies between the working drawings and the specifications.…”
Section: Discussionmentioning
confidence: 99%
“…Steps 1 to 4 should be continued until the error reaches an acceptable level and at this point, the training ends. After training the network by providing it with input vectors, the output vectors simulated by the network can be received [34].…”
Section: Structure Radial Basis Neural Networkmentioning
confidence: 99%
“…Based on the results of another study by Pakseresht and Asgari (2012), identification and ranking of the important factors of success in construction projects of Pars Garma Company was carried out using a questionnaire survey among the 58 members of the management staff, project managers and technical experts [33]. In the same year, with the aim of identifying critical success factors in public housing projects in Ghana and using the experiences of 13 specialists in the field of these projects, a study was conducted by Adinyira et al [34].…”
Section: Consolidated Framework Of Csfs For Construction Projectsmentioning
confidence: 99%